2021
DOI: 10.1007/s10787-021-00806-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathophysiology of coronavirus disease 2019: neuroinflammation and blood brain barrier disruption are critical pathophysiological processes that contribute to the clinical symptoms of SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the novel SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) first discovered in Wuhan, Hubei province, China in December 2019. SARS-CoV-2 has infected several millions of people, resulting in a huge socioeconomic cost and over 2.5 million deaths worldwide. Though the pathogenesis of COVID-19 is not fully understood, data have consistently shown that SARS-CoV-2 mainly affects the respiratory and gastrointestinal tracts. Nevertheless, accumulating evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 280 publications
2
52
0
Order By: Relevance
“…Some have postulated that neurological sequelae of COVID-19 could reflect direct actions of SARS-CoV-2 on the brain ( Boldrini et al, 2021 ; Saleki et al, 2020 ). Indeed, SARS-CoV-2 mRNA has been detected in cerebrospinal fluid (CSF; Moriguchi & Mastorakis, 2020 ), suggesting the virus could either damage ( Welcome et al, 2021 ) or permeate ( Rhea et al, 2021 ) the blood-brain barrier (BBB). To this extent, some have attributed neuropsychiatric manifestations of COVID-19 to disruptions in the BBB that result in atrophy to neural and glial cells ( Alonso-Lana et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some have postulated that neurological sequelae of COVID-19 could reflect direct actions of SARS-CoV-2 on the brain ( Boldrini et al, 2021 ; Saleki et al, 2020 ). Indeed, SARS-CoV-2 mRNA has been detected in cerebrospinal fluid (CSF; Moriguchi & Mastorakis, 2020 ), suggesting the virus could either damage ( Welcome et al, 2021 ) or permeate ( Rhea et al, 2021 ) the blood-brain barrier (BBB). To this extent, some have attributed neuropsychiatric manifestations of COVID-19 to disruptions in the BBB that result in atrophy to neural and glial cells ( Alonso-Lana et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection of the brainstem may also cause respiratory center dysfunctions [59]. Dysregulation of hormone and neurotransmitter signaling have also been suggested to contribute to the neuropathogenic sequelae of SARS-CoV-2 infection [60]. While the mechanisms by which SARS-CoV-2 impairs the CNS are not completely known, neuroinflammation and blood-brain barrier (BBB) disruption have been suggested to contribute to neurological symptoms and poor prognosis [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of hormone and neurotransmitter signaling have also been suggested to contribute to the neuropathogenic sequelae of SARS-CoV-2 infection [60]. While the mechanisms by which SARS-CoV-2 impairs the CNS are not completely known, neuroinflammation and blood-brain barrier (BBB) disruption have been suggested to contribute to neurological symptoms and poor prognosis [60][61][62]. Indeed, profound neuroinflammatory changes have been reported in COVID-19 patients [63], which could be due to direct infection of the CNS, microglia activation, and activated peripheral immune response to SARS-CoV-2 infection [56,64], all of which could be worsened by obesity [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is observed with viruses such as hepatitis E virus (28) and encephalitic alpha viruses (29). Because of the high expression of ACE2 in cellular components of the BBB, it is suggested that the disruption of BBB by SARS-CoV-2 may play the main role in the central and peripheral nervous system damage seen in severe COVID-19 (30).…”
Section: Possible Mechanisms For Entering the Cnsmentioning
confidence: 99%